2020
DOI: 10.1051/e3sconf/202016403017
|View full text |Cite
|
Sign up to set email alerts
|

The process of increasing the stable operation of the working body in crank presses

Abstract: The article considers the study of the synthesized concept of frictional contact of solids in crank presses. As a result of the analysis the possibility of obtaining the maximum load characteristic of the friction contact within the interval of variation of the friction coefficient has been established. The possibility of equality of the values of the friction force of the friction contact at the boundaries of the indicated interval in the presence of a maximum and the achievement of their greatest stability u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hydroconstruction, the withdrawal of a large amount of fresh water for irrigation and other economic needs, the operation of water intakes without fish protection devices, water pollution, excess of the catch quota and other factors have sharply worsened the condition and conditions of fish stock reproduction: fish catches are decreasing (a tense situation for the fish industry has developed in the basins rivers: Ob, Irtysh, Yenisei, Kuban The seas of the Far East are characterized by the disappearance of the sardine -ivasi and a reduction in pollock stocks, which is caused by unregulated foreign fishing; the disappearance of valuable fish species occurs, the oppression and death of many species of ichthyofauna (in the Volga, the natural spawning grounds of white fish have completely disappeared, only 12% of sturgeon fish survived; thickets of seaweed (kelp) in some areas of Primorye have disappeared; the incidence of valuable fish species and the accumulation of harmful pollutants in it are increasing (in the muscle tissues of sturgeons, there is an accumulation of chlororganic pesticides, with lei of heavy metals, mercury). The results of the check showed that organic compounds of pguty were found in 156 out of 193 fish samples from various parts of the Vetluga, Cheboksary and Kuibyshevsky reservoirs in concentrations from 0.005 to 1.0 mg / kg of fish weight [6][7][8].…”
Section: Methodsmentioning
confidence: 99%
“…Hydroconstruction, the withdrawal of a large amount of fresh water for irrigation and other economic needs, the operation of water intakes without fish protection devices, water pollution, excess of the catch quota and other factors have sharply worsened the condition and conditions of fish stock reproduction: fish catches are decreasing (a tense situation for the fish industry has developed in the basins rivers: Ob, Irtysh, Yenisei, Kuban The seas of the Far East are characterized by the disappearance of the sardine -ivasi and a reduction in pollock stocks, which is caused by unregulated foreign fishing; the disappearance of valuable fish species occurs, the oppression and death of many species of ichthyofauna (in the Volga, the natural spawning grounds of white fish have completely disappeared, only 12% of sturgeon fish survived; thickets of seaweed (kelp) in some areas of Primorye have disappeared; the incidence of valuable fish species and the accumulation of harmful pollutants in it are increasing (in the muscle tissues of sturgeons, there is an accumulation of chlororganic pesticides, with lei of heavy metals, mercury). The results of the check showed that organic compounds of pguty were found in 156 out of 193 fish samples from various parts of the Vetluga, Cheboksary and Kuibyshevsky reservoirs in concentrations from 0.005 to 1.0 mg / kg of fish weight [6][7][8].…”
Section: Methodsmentioning
confidence: 99%